2003
DOI: 10.4039/n03-007
|View full text |Cite
|
Sign up to set email alerts
|

Pupation behaviour of western flower thrips (Thysanoptera: Thripidae) on potted chrysanthemum

Abstract: Western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), is a serious pest of greenhouse vegetable and ornamental crops across Canada (Broadbent et al. 1987). Upon completing larval development, F. occidentalis either pupates on their host plant or drops to the ground before pupation occurs (Lewis 1973). Because several soil-dwellers prey on or infect F. occidentalis pupae (Gillespie and Quiring 1990; Helyer et al. 1995), assessing the proportion of individuals that pupate on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
(6 reference statements)
1
15
0
Order By: Relevance
“…Similar published works have recorded recollection rates of about 50-90% (Broadbent et al 2003;Berndt et al 2004;Buitenhuis & Shipp 2008). Low recapture rates appear to be correlated to the size of the experimental area used, with larger plants/arenas having lower recapture rates.…”
Section: Western Flower Thrips Biology Experimentssupporting
confidence: 80%
See 2 more Smart Citations
“…Similar published works have recorded recollection rates of about 50-90% (Broadbent et al 2003;Berndt et al 2004;Buitenhuis & Shipp 2008). Low recapture rates appear to be correlated to the size of the experimental area used, with larger plants/arenas having lower recapture rates.…”
Section: Western Flower Thrips Biology Experimentssupporting
confidence: 80%
“…Literature on pupation and distribution of WFT on gerberas, chrysanthemums and roses is variable, with most suggesting very high levels of WFT pupate in the soil. Studies have found 97% pupation on chrysanthemums (stage unknown), about 90% soil pupation on non-flowering chrysanthemums and flowering and non-flowering roses (Bennison et al 2002a), and only 50-60% soil pupation on flowering chrysanthemums (Broadbent et al 2003;Buitenhuis & Shipp 2008). Only rarely have soil pupation rates been recorded at very low rates, e.g.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…of certain plant types[16] [30] [40] [41]. For example, studies have reported that western flower thrips will pupate in the complex inflorescences (flowers) of chrysanthemum plants[35] [42]. Factors that can influence western flower thrips pupating on plants include: relative humidity, host plant species, and plant growth stage[38] [42].The proportion of western flower thrips that pupate in the growing medium or soil is likely affected by host plant species[43].…”
mentioning
confidence: 99%
“…Larval stages are found on the host whereas pupal stages are usually passed in the soil. Late in the 2nd larval instar, the thrips usually drops to the ground where it pupates and remains there until emergence of the adult (Stannard 1968;Broadbent et al 2003; Morse & Hoddle 2006).…”
mentioning
confidence: 99%